Transcellular activation of the human immunodeficiency virus type 1 long terminal repeat in T lymphocytes requires CD4-gp120 binding. - Marcuzzi, A (J Virol, 1992)
Cells expressing human immunodeficiency virus type 1 (HIV-1) tat can transactivate the HIV-1 long terminal repeat (LTR) in cocultured T lymphocytes. In this report, we describe the molecular requirements for transcellular activation of the LTR in Jurkat cells. An analysis with deletion mutants and blocking antibodies demonstrated a requirement for env expression in addition to tat expression for transcellular activation to occur. The results suggest that the transient association of CD4 and gp120 in cocultured cells is required for tat-mediated transcellular activation. The events that follow CD4-gp120 binding in transactivation, however, do not require the gp120-neutralizing domain, in contrast to HIV-mediated fusion and infection. The consequences of this interaction on cellular function are currently under investigation. IMAGES: